An investigation into the modification of microwave-assisted oxidation in the macromolecular structure of coal via XRD and Raman spectroscopy. (15th April 2023) - Xu, Chaoping; Li, He; Lu, Jiexin; Lu, Yi; Shi, Shiliang; Ye, Qing; Li, Min; Wang, Zheng
Highlights: The evolution of the macromolecular structure of modified coal was investigated. Microwave heating induces the condensation and disordering of aromatic clusters. The oxidation leads to a heterogeneous spatial arrangement of macromolecules. Microwave-assisted oxidation promotes the aromatization and graphitization of coal. Abstract: The macromolecular structure of coal governs the generation and expansion of micro/mesopores, contributing significantly to the storage and transport of coalbed methane (CBM). To reveal the modification mechanism of microwave-assisted oxidation at molecular scale, this paper presents a comprehensive analysis of the evolutionary characteristics of macromolecular structure of coal using X-ray diffraction and Raman spectroscopy tests. Results show that microwave irradiation triggers the conversion of ordered graphitic crystalline carbon to amorphous carbon, as well as the condensation and heterogeneous spatial arrangement of aromatic clusters. The oxidation of N a C l O or N a 2 S 2 O 8 destroys the initial aromatic structure and reduces the aromaticity of coal, whereas Fenton's reagent oxidation causes the cyclocondensation of macromolecular structure and contributes to the graphitization and crystallization of coal. Microwave-assisted oxidation not only facilitates the directional growth of aromatic rings and the cross-linking of aliphatic chains, but also induces the rotation, displacement, stacking and gradual parallel alignment of aromatic lamellae, thus improving the integrity of three-dimensional lattice of graphite structure and the orderliness of macromolecular structure. As the average size of microcrystalline structural units increases and align directionally to form molecularly oriented domains, the pore size and volume subsequently increases, thereby enhancing the gas transport capacity of coal and the extraction of CBM. This study provides theoretical guidance for the optimisation of microwave-assisted oxidant modification and the paramount consideration of CBM development strategy.